CENDEKIAWAN DI TENGAH KRISIS NILAI: SEBUAH REFLEKSI AKSIOLOGIS TENTANG PERAN ILMU PENGETAHUAN - Rahmawati, Milatul; M, U Pg Fitra A.; Nellitawati, Nellitawati; Jasrial, Jasrial; Sulastri, Sulastri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Global society faces a major challenge in the form of a value crisis that affects various aspects of life. The value crisis in contemporary society not only impacts social and cultural aspects, but also touches the realm of science. Science, which should be a tool for seeking truth and enlightenment, often loses its direction due to the dominance of pragmatic, political, and economic interests. In the midst of this situation, the role of scholars becomes very crucial. This article offers an axiological reflection on the moral and social responsibility of a scholar in maintaining the meaning and essential purpose of science. With a philosophical approach to science, especially within the framework of axiology, this article highlights how scholars must be a bridge between science and values, between truth and justice. Through this study, the importance of intellectual integrity, moral courage, and commitment to humanity in carrying out the role of science in the midst of a value crisis is emphasized.